PENGARUH KARAKTERISTIK INDIVIDU, MOTIVASI, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA HOTEL SWASTI ECO COTTAGES DI UBUD - Ni Putu Grivia Oktanaryanti; Agus Wahyudi Salasa Gama; Ni Putu Yeni Astiti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2023)
Development of human resources in the company must be prioritized to improve performance. Employee performance can determine how much the employee's ability to carry out his job duties and be responsible for the work itself. This study aims to determine the effect of each variable that the author examines and what is of benefit in this study is to broaden the author's knowledge of human resources, particularly regarding individual characteristics, motivation, organizational culture, and employee performance at the Swasti Eco Cottages Hotel in Ubud. The development of human resources in the company must be prioritized to improve performance. Employee performance can determine how much the employee's ability to carry out his job duties and be responsible for the work itself. This study aims to determine the effect of each variable that the author examines and what is of benefit in this study is to broaden the author's knowledge of human resources, particularly regarding individual characteristics, motivation, organizational culture, and employee performance at the Swasti Eco Cottages Hotels in Ubud. The results showed that individual characteristics and organizational culture had a positive and significant impact on employee performance. While motivation has no effect on employee performance. Future research can develop this research by using other variables that theoretically have an influence on employee performance, such as work discipline, leadership style, work ethic, work environment, and other variables.